Síntese e aplicação de adsorventes a partir de resíduos agrícolas na remoção de contaminantes emergentes - Sacht, Samara Oliveira (2023)
Pharmaceutical products are emerging contaminants present in the aquatic environment, especially water supplies, whose presence has become an environmental problem due to their chemical characteristics that may present risks to the environment and health. Conventional sewage and water treatments do not effectively remove these compounds, making it necessary to introduce new removal processes. Adsorption is an advanced treatment with better cost-benefit viability due to the possibility of using waste as precursors for adsorbents. Furthermore, the process does not generate toxic by-products, and has shown good results in removing contaminants. Therefore, in this work the adsorption of two drugs, cephalexin and diclofenac sodium, was evaluated on activated carbons (ACs) from agricultural waste (cocoa, coconut and coffee). Cocoa activated carbon was synthesized through simultaneous carbonization and physical activation (with water vapor) inside a horizontal furnace with a heating ramp from 5.0 °C min-1 to 800.0 °C, with water injection at 200.0 °C and with a residence time of 1 hour at 800.0 °C. The water rate was varied in order to obtain the best charcoal from the process. Coffee activated carbon was produced and supplied by the UFES Carbonous Materials Laboratory. Commercial coconut charcoal from BahiaCarbon was used for comparison. The CAs were characterized by the following techniques: specific surface area, thermogravimetry, x-ray diffraction, infrared, scanning electron microscopy, nuclear magnetic resonance, pH point of zero charge. The characterization results showed that commercial coconut charcoal has fewer inorganic compounds, neutral pHpcz and an organized structure with a greater surface area (ASE 630 m².g-1). Cocoa and coffee charcoals showed impurities related to calcium and potassium oxides and carbonate and basic pHpcz. In the kinetic study of diclofenac and cephalexin in aqueous solution, the best fit was to the pseudo second order model for all adsorbents. As for the balance study, for the removal of cephalexin, all charcoals adjusted to the Langmuir model. As for the contaminant diclofenac, only the adsorption on coffee charcoal was better adjusted to the Freundlich model, while that of coconut and cocoa were better adjusted to the Langmuir model.